Effect of plasma processing parameters on the surface modification of fibre reinforced composites by atmospheric pressure plasma treatment - Frumosu, Lydia; Bishop, Alex; Castelli, Marco; Bennett, Adam; Nicholls, John R.; Huang, Zhaorong (euspen, 2021)
This report presents a study on the effect of microwave plasma sources on the surface modification of carbon fibre reinforced composites. The adhesion property of polymer composites is an important consideration in manufacturing processes. A key challenge in polymer adhesion is the need for adhesive pre-treatment to improve the wettability properties of the surface. Often three sequential steps are needed: contaminant removal, physically induced surface modification and chemical treatment. Atmospheric plasma treatment (APT) has been shown to either achieve, or eliminate the need for, one or more of these steps. The effects of APT on the surface properties of thermoplastics and thermosetting polymers have been reported recently, but the report on the effect of different plasma sources on the APT of polymers is limited. 50% carbon fibre epoxy samples were subjected to a microwave plasma source with varied flow rate, power, and samples’ distance from source, under atmospheric conditions. The surface energy of the composites was determined using liquid contact angle analysis. A coherence scanning interferometer was used to characterise the surface changes. The underlying mechanisms for the observed change of surface properties will be discussed.
Keywords: Composite; plasma; surface energy; polymers; surface roughness; microwave plasma